A3.22 Upregulated microRNA-182 Expression is Associated with Enhanced Conventional CD4+ T Cell Proliferation in SLE. (25th February 2013) - Alexander, Tobias; Haftmann, Claudia; Templin, Lars; Humrich, Jens; Burmester, Gerd-Rüdiger; Radbruch, Andreas; Hiepe, Falk; Mashreghi, Mir-Farzin
Abstract : Background: Recent reports have shown dysregulated microRNAs (miRNAs) in murine models of lupus, among them increased expression of miRNA-182, which has been demonstrated to target the transcription factor FOXO1 in activated murine CD4 + T cells. The loss of FOXO1 activity in T cells is associated with spontaneous T cell activation, clonal expansion and autoantibody production, all of which are present in systemic lupus erythematosus (SLE). Methods: Expression levels of microRNA-182 (miR-182) and FOXO1 were analysed with RT-PCR in freshly isolated and magnetic purified peripheral blood CD4 + T cells from 9 patients with SLE and age/sex-matched healthy controls (HC). Multicolor flow cytometry was performed to analyse CD4 + T cell expression for CCR7, CD45RA, Ki-67, Foxp3, the interleukin-7 receptor-α (CD127) and phosphorylated STAT-5a (pSTAT5). Analysis of serum IL-7 levels was performed with ELISA in 27 SLE patients and HC (R&D systems). The Wilcoxon signed-rank test was used for statistical analysis. Results: MiRNA-182 was significantly upregulated in CD4 + T cells from SLE patients compared to HC (median relative expression 8.89 × 10E-7 versus 3.96 × 10E-7, p = 0.008) while FOXO1 mRNA levels were decreased, yet without reaching statistical significance. Analysis of Ki-67 expression revealed an increased percentage of proliferating CD4 + T cells in SLE (5.23% versus 2.21%, p = 0.006), which was more prominent in Foxp3 - conventional T cells (Tcons) than in Foxp3 + regulatory T cells (Tregs). Overall, CD4 + T cellular proliferation in SLE was associated with increased frequencies of CD45RA – CCR7 – effector memory T cells and enhanced basal pSTAT5 levels (median MFI 503.5 versus 399.0, p = 0.010), suggesting a recent stimulation with common gamma chain(γc)-signalling cytokines. In this regard, Tcons from SLE samples displayed decreased expression levels for the FOXO1 target gene CD127 (MFI 2021 versus 2553, p = 0.049) and serum IL-7 levels were significantly higher in SLE when compared to HC (17.0 pg/ml versus 10.2 pg/ml, p = 0.001). Conclusions: MiR-182 expression has been shown to be directly dependent on STAT5 activation and to promote the clonal expansion of murine activated CD4 + T cells. Our data suggest that enhanced IL7R/STAT5 signalling presumably mediates the induction of miR182 expression, which in turn promotes the proliferation of Tcons in SLE. The relative contribution of IL7R/miR-182/FOXO1 axis on the enhanced proliferative capacity of SLE Tcons remains elusive and merit further investigation. Collectively, our data provide new insights in the pathophysiology of T cell hyper- activity in SLE and identifies miR-182 as a candidate target for future therapeutic approaches.